Plasma phosphatidylcholine hydroperoxide as a new marker of oxidative stress in alcoholic patients - Junko Adachi; Sachio Matsushita; Naoki Yoshioka; Rika Funae; Tetsuo Fujita; Susumu Higuchi; Yasuhiro Ueno (Journal of Lipid Research, 2004)
Quantitative analysis of plasma phosphatidylcholine hydroperoxide (PCOOH) is an important step in evaluating the biochemical processes leading to oxidative injury. However, secondary products of lipid peroxidation are now used as indices. One hundred nine alcoholic patients, aged 22–81 years (mean ± SEM, 52.0 ± 1.3 years), and 21 healthy volunteers, aged 41–79 years (51.2 ± 2.2 years), participated in this study. Plasma PCOOH was measured by HPLC with chemiluminescence detection. Plasma PCOOH concentration was significantly higher in alcoholic patients (46.1 ± 4.1 pmol/ml) than in controls (15.6 ± 1.8 pmol/ml). It was significantly higher in patients with blood alcohol (88.0 ± 10.5 pmol/ml) than in those without alcohol (32.6 ± 3.1 pmol/ml). The patients with high levels of aspartate aminotransferase, alanine aminotransferase, γ-glutamyl transpeptidase (γ-GTP), and triglyceride (TG) showed significantly higher PCOOH concentrations than did patients with normal levels. The PCOOH level was positively correlated with levels of γ-GTP, HDL, blood alcohol concentration, and TG. Plasma PCOOH levels in 29 alcoholic patients after a 6 week abstinence were decreased significantly (22.8 ± 11.1 pmol/ml), which was associated with improvement on liver function tests. This is the first measurement of plasma PCOOH in alcoholic patients.These results suggest the involvement of lipid peroxidation in alcohol-induced liver damage and confirm that the PCOOH plasma concentration is a new marker of alcohol consumption as well as oxidative stress in alcoholic patients.